Η mesons in hot magnetized nuclear matter. (1st February 2022) - Kumar, Rajesh; Kumar, Arvind
Abstract: interactions are investigated in hot magnetized asymmetric nuclear matter using the chiral SU (3) model and chiral perturbation theory (ChPT). In the chiral model, the in-medium properties of η -mesons are calculated using medium modified scalar densities under the influence of an external magnetic field. Further, in a combined chiral model and ChPT approach, off-shell contributions of the interactions are evaluated from the ChPT effective Lagrangian, and the in-medium effect of scalar densities are incorporated from the chiral SU (3) model. We find that the magnetic field has a significant effect on the in-medium mass and optical potential of η mesons, and we observe a deeper mass-shift in the combined chiral model and ChPT approach than in the solo chiral SU (3) model. In both approaches, no additional mass-shift is observed due to the uncharged nature of η mesons in the presence of a magnetic field.